Inside Cover: Chimeric RNA Oligonucleotides with Triazole and Phosphate Linkages: Synthesis and RNA Interference (Chem. Asian J. 12/2015). Issue 12 (16th November 2015) - Fujino, Tomoko; Kogashi, Kanako; Okada, Koudai; Mattarella, Martin; Suzuki, Takeru; Yasumoto, Kenichi; Sogawa, Kazuhiro; Isobe, Hiroyuki
Abstract : A triazole linkage embedded in a 21‐mer RNA oligonucleotide has been favorably accepted by the Argonaute protein for RNA interference. Researchers at Tohoku University now report structure–activity relationship studies with a series of chimeric oligonucleotides. Their robust synthesis is backed up by a combination of click chemistry and solid‐phase phosphoramidite synthesis, which enables the synthesis of chimeric oligonucleotides of any given sequence possessing triazole linkages at any desired positions. More information can be found in the Full Paper by Hiroyuki Isobe et al. (DOI:10.1002/asia.201500765 ).